Dead man's puzzle [large type] - Hall, Parnell (Hall, Parnell. Puzzle Lady mystery., 2009)
Chief Harper comes to Cora Felton, asking her to solve a crossword puzzle found on the body of old man Overmeyer. Small problem. Cora's niece, Sherry, who is off on her honeymoon, actually writes Cora's crossword puzzle column for her. So Cora pokes into Overmeyer's death, hoping to prove he died of natural causes. But she soon learns that the cranky hermit was the sole surviving member of a stock pooling agreement - and now the town is full of heirs.